Costulatotheca schleigeri (Hyolitha: Orthothecida) from the Walhalla Group (Early Devonian) at Mount Pleasant, central Victoria, Australia. Issue 2 (3rd April 2019) - Earp, Clement
Abstract : Earp, C., 29 January 2019. Costulatotheca schleigeri (Hyolitha: Orthothecida) from the Walhalla Group (Early Devonian) at Mount Pleasant, central Victoria, Australia. Alcheringa. Alcheringa 43, 220–227. ISSN 0311-5518 A number of hyolith fragments (including one operculum), found in Early Devonian marine turbidites at Mt Pleasant, near Alexandra, central Victoria, are described as Costulatotheca schleigeri gen. et sp. nov., the first confirmed record of the order Orthothecida in the Devonian of Australia. Index fossils found at this locality ( Uncinatograptus sp. cf. U. thomasi and Nowakia sp. ex gr. N. acuaria ) indicate an age of Pragian or earliest Emsian. The taphonomy of rare rafted shelly fossils indicates that flysch deposition occurred in a very-low-energy environment into which there were occasional bursts of high-energy turbidites carrying allochthonous fossils from shallower water. Clement Earp [omaiosys@yahoo.com.au ], 1 De Havilland Place, Onerahi, Whangarei 0110, New Zealand .